L-Arginine is essential for pancreatic β-cell functional integrity, metabolism and defense from inflammatory challenge - Krause, M.; McClenaghan, N.; Flatt, P.; Hamem de Bittencourt, P.; Murphy, C.; Newsholme, Philip (BioScientifica Ltd., 2011)
In this work, our aim was to determine whether L-arginine (a known insulinotropic amino acid) can promote a shift of β-cell intermediary metabolism favoring glutathione (GSH) and glutathione disulfide (GSSG) antioxidant responses, stimulus–secretion coupling and functional integrity. Clonal BRIN-BD11 β-cells and mouse islets were cultured for 24 h at various L-arginine concentrations (0–1.15 mmol/l) in the absence or presence of a proinflammatory cytokine cocktail (interleukin 1β, tumour necrosis factor α and interferon γ). Cells were assessed for viability, insulin secretion, GSH, GSSG, glutamate, nitric oxide (NO), superoxide, urea, lactate and for the consumption of glucose and glutamine. Protein levels of NO synthase-2, AMP-activated protein kinase (AMPK) and the heat shock protein 72 (HSP72) were also evaluated. We found that L-arginine at 1.15 mmol/l attenuated the loss of β-cell viability observed in the presence of proinflammatory cytokines. L-Arginine increased total cellular GSH and glutamate levels but reduced the GSSG/GSH ratio and glutamate release. The amino acid stimulated glucose consumption in the presence of cytokines while also stimulating AMPK phosphorylation and HSP72 expression. Proinflammatory cytokines reduced, by at least 50%, chronic (24 h) insulin secretion, an effect partially attenuated b y L-arginine. Acute insulin secretion was robustly stimulated by L-arginine but this effect was abolished in the presence of cytokines. We conclude that L-arginine can stimulate β-cell insulin secretion, antioxidant and protective responses, enabling increased functional integrity of β-cells and islets in the presence of proinflammatory cytokines. Glucose consumption and intermediary metabolism were increased by L-arginine. These results highlight the importance of L-arginine availability for β-cells during inflammatory challenge.